Integrating Economic Changes into Vocational Education Curricula in Land Transportation Schools in Indonesia - Ilham, Ilham (Westscience Press, 2025)
This study examines how economic changes affect the adaptation of vocational education curricula in land transportation schools in Indonesia. Using a mixed-methods approach combining quantitative analysis with SEM-PLS and qualitative analysis via NVivo, this research identifies the significant impact of inflation, unemployment, and government policies on curriculum adjustments. Findings show that economic factors directly influence curriculum changes, necessitating continuous updates to align with industry needs and the labor market. Socio-cultural factors including parental education, lifestyle shifts, and cultural traditions also shape curriculum relevance and effectiveness. Government policies serve as a critical enabler, facilitating timely responses to economic and labor market fluctuations through funding, regulation, and institutional collaboration. The study confirms that curriculum responsiveness requires a holistic framework integrating economic signals, policy support, industry alignment, and local socio-cultural contexts. Based on these insights, the research offers practical recommendations to enhance curriculum relevance through stronger coordination among government, industry, and educational institutions. These include continuous economic monitoring, modular curriculum design, localized content development, and expanded industry-based training. The findings contribute to both empirical understanding and policy discourse on vocational education reform in dynamic economic environments.